Understanding programming languages - Ben-Ari, M., 1948- (Chichester ; New York : John Wiley and Sons, 1996)
Introduction to programming languages. Essential concepts. Advanced concepts. Programming large systems. Non-imperative programming languages.
Keywords: Computer; Electronic computers; Programming languages; Programming languages (Electronic computers)